Mahaim fiber connecting the right atrium to the left ventricle: a case report. Issue 4 (1st June 2020) - Yakabe, Daisuke; Fukuyama, Yusuke; Araki, Masahiro; Aso, Akemi; Nakamura, Toshihiro
Abstract: In the majority of cases presenting with the Mahaim fiber (MF), the MF connects the lateral right atrium (RA) to the right bundle branch or the right ventricle. We present the case of a 33‐year‐old man with antidromic atrioventricular reentrant tachycardia using MF connected to the septal RA and left ventricle (LV). Although the Mahaim potential was recorded at the septal RA, ablation at this site could not eliminate the MF and had a potential risk of injury to the atrioventricular node. Additional application at the posterior septal LV achieved successful MF ablation. Abstract : Mahaim fiber was located between septal right atrium and posterior left ventricle (LV). Successful ablation was achieved at the posterior LV.